STRUCTURAL CHANGES AND CONVERGENCE IN EU AND IN ADRIATIC-BALKANS REGION - Lucian-Liviu Albu (European Regional Science Association (ERSA), 2011)
Coming from standard economic growth theory and empirical evidences, we concentrated on the convergence process as a result of structural changes in economy. We investigate the differences among countries in EU in terms of the share in total economy of main sectors. Then, based on the spatial (empirical) distribution of such shares in EU we are proposing a model to estimate a typology of the convergence process in the European area. Taking into account the existing differences among sectors in matter of productivity, there are two versions of the model: considering the share of sectors in total employment and the share of sectors in GDP respectively. Moreover, we developed several modelling schemes that could be useful to improve the strategies oriented to achieve a real convergence in EU and further in Adriatic-Balkans region. In this way, we can obtain simulations from a country or group of countries (European Union, for example) on long term and quantifying the impact of structural changes on the convergence process. Indeed, the actual global crisis seems to influence negatively the convergence process in EU. As a rule, just new adhered countries were more affected by the actual crisis. Today all forecasts are suffering by uncertainty. Thus, further efforts must be allocated to evaluate the negative impact of actual crisis on the convergence process.
Keywords: 330